Which is false: Oxaliplatin or fluoropyrimidine? An analysis of patients with KRAS wild‐type metastatic colorectal cancer treated with first‐line epidermal growth factor receptor monoclonal antibody. Issue 10 (30th July 2013) - Wen, Feng; Tang, Ruilei; Sang, Yaxiong; Li, Meng; Hu, Qiancheng; Du, Zedong; Zhou, Yi; Zhang, Pengfei; He, Xiaofeng; Li, Qiu
Abstract : This meta‐analysis was performed to determine whether the addition of monoclonal antibodies (mAbs) of epidermal growth factor receptor (EGFR) to oxaliplatin‐based chemotherapy treatment improves efficacy in KRAS wild‐type metastatic colorectal cancer (mCRC), and whether infusional 5‐fluorouracil (5‐FU) and oxaliplatin is a preferred combination for EGFR mAbs. Oxaliplatin (including treatment), EGFR mAbs, first‐line treatment, KRAS wild‐type, and mCRC were used as key words. The PRIME, OPUS, COIN, and NORDIC VII trials were identified by two independent authors. Time‐to‐event outcomes of overall survival (OS) and progression‐free survival (PFS) were analyzed using HRs (hazard ratios) with fixed effect, and response rate (RR) using odd ratios (OR) with fixed effect. A total of 1767 patients who were KRAS wild‐type were included in this meta‐analysis, with 866 patients in the mAbs and chemotherapy combination group and 901 patients in the chemotherapy alone group. The addition of mAbs to oxaliplatin‐based chemotherapy in patients with KRAS wild‐type mCRC as first‐line treatment resulted in significant improvements in PFS (HR = 0.88; 95% confidence interval (CI), 0.79–0.99; P =  0.03) and response rate (RR) (OR = 1.38; 95% CI, 1.14–1.66; P  =   0.009) compared with chemotherapy alone, but the difference in OS was not significant (HR = 0.96; 95% CI, 0.85–1.08; P =  0.48). However, the differences in OS and PFS were not significant when mAbs were added to bolus 5‐FU or capecitabine‐based regimens compared with chemotherapy alone, whereas PFS improved with an infusional 5‐FU and oxaliplatin combination ( P =  0.06; PFS, HR = 0.76; 95% CI, 0.65–0.86; P =  0.0002), and even OS was marginally significant, which was consistent with the subgroup analysis of cetuximab and panitumumab. EGFR mAbs combined with oxaliplatin and an infusional 5‐FU regimen was associated with significantly improved RR, PFS and OS as first‐line treatment in KRAS wild‐type mCRC.